Modernization and sport: The reform of Sport England and UK Sport - Houlihan, B.; Green, M. (Public Administration, 2009)
This article evaluates the impact of New Labour`s `modernization project` on two key non-departmental public bodies for sport, Sport England and UK Sport. Our analysis concentrates on identifying the sources of the general momentum for modernization in the sport sector, how it has been interpreted by government in relation to the two organizations, the nature and consequences of modernization for both organizations, and the future of modernization. The analysis is informed by a range of public documents produced by government and by the two sports agencies, together with a series of seven interviews conducted with senior staff and members of Sport England and UK Sport and with senior civil servants in the Department for Culture, Media and Sport. Our conclusions suggest that modernization has resulted in a narrowing of the two organizations` objectives, the adoption of business-like principles and a `command and control` regime in relationships with key frontline delivery partners.